O que acontece durante o recreio em duas escolas da cidade de Jaú com crianças do 2º e 3º ano do ensino fundamental - Vieira, Thiago Martines [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work had how I aim to notice what it happens in the recreation of two schools of basic teaching I, more precisely with children of the 2nd and 3rd year, analysing what they do and since they play. The interest in observing this moment is the fact of, at present, the children they have not many places to play, principally due to the violence and gradually places with structure for the same thing; the streets are already not any more places where the child can play the friends calmly, interact with other, his turn discovers the world and principally to enjoy itself. With these facts the school becomes the most appropriate place so that the child can play and interact with other children and at the same time to be protected leaving so the most carefree parents. The school becomes the great back yard in the life of the child, when several activities are happening there more and in this way developing not only the communication, the spirit of collaboration and of companionship, the co-ordination motora in general and the autonomy. Therefore the recreation makes an important time into the school life, moment in which the child can practise the universal right that is secured of playing

Esse trabalho teve como objetivo observar o que acontece no recreio de duas escolas de ensino fundamental I, mais precisamente com crianças do 2º e 3º ano, analisando o que elas fazem e como elas brincam. O interesse em observar esse momento é o fato de, atualmente, as crianças não possuírem muitos lugares para brincar, principalmente devido à violência e aos poucos lugares com estrutura para o mesmo; as ruas já não são mais lugares onde a criança pode brincar com os amigos tranquilamente, interagir com o outro, descobrir o mundo a sua volta e principalmente se divertir. Com esses fatos a escola se torna o local mais apropriado para que a criança possa brincar e interagir com outras crianças e ao mesmo tempo estar protegida deixando assim os pais mais despreocupados. A escola se torna o grande quintal na vida da criança, acontecendo ali as mais diversas atividades e dessa maneira desenvolvendo não só a comunicação, o espírito de colaboração e de companheirismo, a coordenação motora em geral e a autonomia. Por isso o recreio se torna um tempo importante na vida escolar, momento no qual a criança pode exercer o direito universal que lhe é assegurado de brincar
Keywords: Estudantes - Recreação; Brincadeiras; Interação social em crianças; Escolas; Students; Recreation; Play; Social interaction in children; Schools